Benefits of Control, Capital Structure and Company Growth - Elisabeth Mueller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper studies the influence of the private benefits of control on the capital structure and the growth of private companies. It is argued that companies in which existing owners would lose more control if they expanded, have smaller equity increases, are more highly levered and grow more slowly. The dataset covers 8,964 private UK companies with limited liability for up to 5 years. Potential loss of control is measured as the difference in the probability of winning a vote for the largest owner before and after a hypothetical equity increase. Consistent with the private benefits of control, the results show that companies with a high potential loss of control do indeed have smaller equity increases, use more debt and grow more slowly.
More recent version: http://hdl.handle.net/10419/24494
Keywords: G32; G34; 330; benefits of control; capital structure; company growth; small and medium-sized enterprises; entrepreneurship; Corporate Governance; Kapitalstruktur; Unternehmenswachstum; Großbritannien